KEBIJAKAN KOLONIAL DALAM MANAJEMEN PENDIDIKAN KRISTEN DI INDONESIA SEBELUM MASA POLITIK ETIS - Kemas Badaruddin; Siti Zaila; Mirrah Salsabila; Syahrul Ramadhan (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
The field of education in the colonial era is often studied in the context of the implementation of the Ethical Policy, one of which is based on the speech of Queen Wilhelmina in 1901 which emphasized that the Netherlands is a Christian country and is committed to helping the mission of that religion. This research attempts to answer the formulation of questions about political policies in Christian education management prior to the Ethical Politics period. The methodology used is a historical research type by going through literature searches, evaluating, verifying, and synthesizing evidence from the data collected. The results of this study indicate that education management policies have been pursued by the Vereenigde Oostindische Compagnie (VOC) since the early 17th century, where due to the influence of religious wars, this trading partnership also tried to replace Portuguese domination and Catholicism in Indonesia. The form of education in that era was still simple to teach obedience and religious rituals in individual teaching without class levels. Apart from a shortage of experienced educators, Dutch language was less popular than Portuguese and Malay. After the company collapsed in 1799, the Dutch government was neutral towards religious affairs since 1808. This caused many "Zending" (Protestant Evangelism) bodies to spread religion as well as establish a number of educational institutions as happened in Minahasa (since the 1830s) and in Batak lands (since the 1860s).